Renewing Local Planning to Face Climate Change in the Tropics - Tiepolo, Maurizio; Pezzoli, Alessandro; Tarchiani, Vieri (Green Energy and Technology, 2017)
climate vulnerability; urban resilience; climate change; adaptation; planning; environmental risk analysis; decision making; disaster risk reduction; tropical climate management